Technological change: History, theory and measurement. A brief account - Heinz D. Kurz; Rita Strohmaier; Mark Knell (European Commission, Joint Research Centre (JRC), 2025)
Technological change, an overwhelming fact in recent socioeconomic history, involves, as Joseph A. Schumpeter famously put it, "creative destruction" on a large scale: it gives rise to new goods, production methods, firms, organisations, and jobs, while rendering some received ones obsolete. Its impact extends beyond the economy and affects society, culture, politics, and the mind-set of people. While it allows solving certain problems, it causes new ones, inducing further technological change. Against this background, the paper attempts to provide a detailed, yet concise exploration of the historical evolution and measurement of technological change in economics. It touches upon various questions that have been raised since Adam Smith and by economic and social theorists after him until today living through several waves of new technologies. These questions include: (1) Which concepts and theories did the leading authors elaborate to describe and analyse the various forms of technological progress they observed? (2) Did they think that different forms of technological progress requested the elaboration of different concepts and theories - horses for courses, so to speak? (3) How do different forms of technological progress affect and are shaped by various strata and classes of society? Issues such as these have become particularly crucial in the context of the digitisation of the economy and the widespread use of AI. Finally, the paper explores the impact of emerging technologies on the established theoretical frameworks and empirical measurements of technological change, points to new measurements linked to the rise of these technologies, and evaluates their pros and cons vis-à-vis traditional approaches.
Keywords: 330; technological change; classical economics; neoclassical economics; growth accounting; endogenous growth; evolutionary economics; sociotechnical studies; GPTs; digitalisation; AI